Parcours autour de la notion d’apprentissage collaboratif : didactique des langues et numérique - Claude Springer (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article is devoted to a theoretical review of the notion of collaborative learning. Higher education as well as schools in general experiment different learning situations that take an active approach claiming more or less collaborative learning. At the same time, the social web has developed through exchanges, sharing and collaboration. Collaborative learning thus seems to be back in fashion. We are seeking out different didactic and theoretical propositions, particularly those concerning collaborative learning in language teaching and in distance learning, to elaborate our reflection. We propose, finally, a definition for new digital learning devices centered on creative projects. This theoretical reflection should enable university pedagogy to take into account a collaborative learning approach explicitly assumed as a means for attaining a citizenship education.